Economic Benefits of a Routine Second Dose of Combined Measles, Mumps and Rubella Vaccine in Canada - Marc Rivière (Canadian Journal of Infectious Diseases, 1997)
OBJECTIVE: To evaluate the potential economic benefits of a program for a second routine dose of combined measles, mumps and rubella (MMR) vaccine, administered to children in Canada.